2011
DOI: 10.1007/s10811-011-9701-4
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Pyrodinium bahamense var. compressum and associated cultivable bacteria to antibiotic treatment

Abstract: Pyrodinium bahamense var. compressum is a toxic dinoflagellate that produces paralytic shellfish poisoning toxins. It is responsible for the chronic toxicity of shellfish in many coastal areas of the Philippines and other South East Asian countries. For the purpose of using antibiotic treatment to possibly generate axenic cultures and understand their growth requirements, the antibiotic tolerances of two local P. bahamense var. compressum isolates and their associated bacteria were determined. The antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is possible that free-living bacteria in the medium or in the field could enter the intracellular environment through these 'breaks' and become trapped as the cell developed a new amphiesmal layer and thecal wall. This mechanism has not yet been reported in any species of dinoflagellates or microalgae, the majority of which have been shown to harbour bacterial endosymbionts including Pyrodinium Onda, 2011;Santos & Azanza, 2012). More studies, perhaps using labelling and time-lapse microscopy, should be done to elucidate this hypothesis and to determine any specificity in the establishment of the endosymbionts in the host cell.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that free-living bacteria in the medium or in the field could enter the intracellular environment through these 'breaks' and become trapped as the cell developed a new amphiesmal layer and thecal wall. This mechanism has not yet been reported in any species of dinoflagellates or microalgae, the majority of which have been shown to harbour bacterial endosymbionts including Pyrodinium Onda, 2011;Santos & Azanza, 2012). More studies, perhaps using labelling and time-lapse microscopy, should be done to elucidate this hypothesis and to determine any specificity in the establishment of the endosymbionts in the host cell.…”
Section: Discussionmentioning
confidence: 95%
“…These associations and their still unknown interactions may be truly significant that their removal from the host and/or disruption of the association may be detrimental to the host alga. For example, loss of viability of cultured Pyrodinium was observed when associated cultivable bacteria were attempted to be removed by antibiotic treatment (Santos and Azanza 2012). These results are the foundations of our ongoing investigations to further understand the significance of the "microalgal microbiome" in such ecological relationships using high-throughput sequencing approach.…”
Section: Bacteria-algae Associationmentioning
confidence: 94%
“…Identifying these intracellular bacteria is a crucial step toward the elucidation of their roles in the biology and ecology of dinoflagellates. For example, recent evidence showed that the removal of culturable and possibly most bacteria by antibiotic treatment significantly affected the growth or caused death of Pyrodinium cultures (Santos and Azanza 2012). They have also been implicated in the initiation, maintenance and decline of algal blooms (Doucette 1995).…”
Section: Introductionmentioning
confidence: 99%